2009
DOI: 10.1016/j.tecto.2008.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Deep structure of the western South African passive margin — Results of a combined approach of seismic, gravity and isostatic investigations

Abstract: The passive margin of the South Atlantic shows typical features of a rifted volcanic continental margin, encompassing seaward dipping reflectors, continental flood basalts and high-velocity/density lower crust at the continentocean transition, probably emplaced during initial seafloor spreading in the Early Cretaceous.The Springbok profile offshore western South Africa is a combined transect of reflection and refraction seismic data. This paper addresses the analysis of the seismic velocity structure in combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 41 publications
7
75
0
Order By: Relevance
“…The fourth traverse is located at about 30 • S (Fig. 1, line 7) and the seismic velocity profile derived by Hirsch et al (2009) shows a well-developed body of HVLC below SDRs. Finally, it is worth mentioning for reference that Stankiewicz et al (2008) published a seismic velocity profile ( Fig.…”
Section: Existing Profiles and Interpretationmentioning
confidence: 94%
See 1 more Smart Citation
“…The fourth traverse is located at about 30 • S (Fig. 1, line 7) and the seismic velocity profile derived by Hirsch et al (2009) shows a well-developed body of HVLC below SDRs. Finally, it is worth mentioning for reference that Stankiewicz et al (2008) published a seismic velocity profile ( Fig.…”
Section: Existing Profiles and Interpretationmentioning
confidence: 94%
“…In contrast to the reasonable spatial coverage of seismic reflection data, wide-angle seismic lines are few, especially on the South American margin, which motivated the new studies reported below. To some extent, gaps in the seismic coverage can be compensated for by regional gravity interpretations (e.g., Blaich et al, 2009Blaich et al, , 2011Dragoi-Stavar and Hall, 2009;Maystrenko et al, 2013;Franke et al, 2006;Hirsch et al, 2009). …”
Section: Existing Profiles and Interpretationmentioning
confidence: 99%
“…the case of a volcanic margin such as the Uruguay one, the weakness of the crust could be related to the high heat flow related to the emerging plume and/or to the important syn-tectonic underplating and impregnation of the lower crust by magmatic melts (Franke et al, 2006;Hirsch et al, 2009). On the conjugate margin of Namibia/South Africa, high seismic velocities (up to >7 km/s) also point to a gabbroic composition of the lower crust (Fromm et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Namaqua-Natal metamorphic terranes (NNMB): R = Richtersveld; G = Gordonia; B= Bushmanland of the Namaqua province; N = Natal province. Black = Green and Durrheim (1990), Mahanyele et al (2004), Hirsch et al (2008); Lines on the South coast: light grey line = onland seismic refraction line of Stankiewicz et al (2007;2008) and the longer onshore-offshore seismic refraction line (Stankiewicz et al 2008;Parsiegla et al 2007;; black line perpendicular to CFB front = IyA-The regions with complex reflectivity patterns cross-cut by the high conductivity anomalies in the mid-crust (Figures 7 and 9) could also be interpreted as ore bodies, since ore minerals such as Pyrrhotite and other iron sulphides have a high conductivity. Impedance spectroscopy on samples from boreholes SA-1/66 and KW-1/67, proved high conductivity in the Wh/PA Formations, associated with pyrite and chalcopyrite (Branch et al, 2007).…”
Section: Deep Crustal Profile Southern Karoo Basin and Beattie Magnementioning
confidence: 99%